2017
DOI: 10.1186/s12974-017-0938-y
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Autism Spectrum Disorders and Schizophrenia through inflammation and biomarkers - pre-clinical and clinical investigations

Abstract: In recent years, evidence supporting a link between inflammation and neuropsychiatric disorders has been mounting. Autism spectrum disorders (ASD) and schizophrenia share some clinical similarities which we hypothesize might reflect the same biological basis, namely, in terms of inflammation. However, the diagnosis of ASD and schizophrenia relies solely on clinical symptoms, and to date, there is no clinically useful biomarker to diagnose or monitor the course of such illnesses. The focus of this review is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 275 publications
6
71
0
3
Order By: Relevance
“…These overlapping genes impact brain structures and dopamine homeostasis [Khanzada, Butler, & Manzardo, ]. Finally, a recent study reported that both schizophrenia and ASD were associated with inflammation [Prata et al, ]. These results indicated that schizophrenia is related to ASD, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These overlapping genes impact brain structures and dopamine homeostasis [Khanzada, Butler, & Manzardo, ]. Finally, a recent study reported that both schizophrenia and ASD were associated with inflammation [Prata et al, ]. These results indicated that schizophrenia is related to ASD, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Schizophrenia and ASD are reported to share some similar apparent [Cauda et al, ; Kocovska, Gaughran, Krivoy, & Meier, ; Lionel et al, ]. There is genetic, environmental, imaging, neurochemical, and inflammation evidence for a connection between schizophrenia and ASD [Cauda et al, ; Fiksinski et al, ; Kocovska et al, ; Pavăl, ; Prata, Santos, Almeida, Coelho, & Barbosa, ]. Recently, some scientists have focused on the association between schizophrenia and ASD [Abdallah et al, ; Bakken et al, ; Bradley, Summers, Wood, & Bryson, ; Fiksinski et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The disorders considered in the present review are caused by different etiologic factors and display a variety of symptoms that could hardly be reconducted to a unifying pattern. However, regardless of the origin of these diseases, the involvement of processes which share aspects reasonably attributable to inflammation is detectable in their underlying pathogenic mechanisms (Giovannoni et al 2007;Wilcock and Griffin 2013;King et al 2014;Ochoa-Cortes et al 2016;Hamlett et al 2018;Stark et al 2016;Chitnis and Weiner 2017;Labzin et al 2018;Fehily and Fitzgerald 2017;Mizuma and Yenari 2017;Neal and Richardson 2017;Franklin et al 2017;Prata et al 2017;Santos and Ferreira 2017;Joshi and Singh 2017;Thelin et al 2017a;Majd et al 2017;Zhang et al 2017;Zolezzi and Inestrosa 2017). This consideration has also been the object of a recent valuable review (Skaper et al 2018).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In fact, reports have shown a significant association between AnxA1 gene duplication and autism 63 or single nucleotide polymorphism in AnxA1 gene and schizophrenia 64 , bipolar disorder or depression 65 . Most intriguingly, all these conditions have been often linked to immune dysfunctions or inflammatory conditions [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%